THE STARTING ANGLE OF THE BALL AND THEIR RELATIONSHIP WITH THE TWO ANGLES FALL AND REBOUND THE BALL OF TOPSPIN SERVE FOR THE NATIONAL TENNIS TEAM PLAYERS - Thamr, Ahmed; Abdul Abbas, Hammam (Journal of Physical Education, 2015)
Tennis has been seen a remarkable development at the global level on both sides skills and physical that was by motor analyzing for the skills of the game contribution with the rest of other sciences to know the strengths and weaknesses affecting in the performance of each skill, and the analysis of the game of tennis skills by studying biomechanics it variables which works to detect errors and the strengths and weaknesses in motor performance and provide information that cannot with the normal eye, because most of the skills of the game of tennis advantage in speed and accuracy of performance, by that the importance of research it's came by finding out the relationship between the angle of the start of the ball and the corners of the fall and rebound the ball to the skill of the serve to rotate the top for players of national team, and to make the ball reach higher amount of accuracy needed for its performance as the best, and through follow-up by researcher to exercise tennis for most of the players of Iraq and all categories and by being one of the practitioners of the game of tennis there found the lack of attention most of the trainers mechanical variables when training which was reason a weak when with most of the players at the performance of any Type of serve types, in particular angle of starting , falling and rebound of ball, researcher has chosen descriptive approach to achieve the goals of his research, and chose his sample by deliberate way and that was the top four players labeled in Iraq, researcher test serve on the sample in the experience of the major search and extract variables using fast camera, and then statistically treated, and by that way the researcher reach the results of his research and recommended some of the recommendations